1998
DOI: 10.1016/s0248-4900(98)80017-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural characterization of atrial natriuretic peptide receptors (ANP‐R) mRNA expression in rat kidney cortex

Abstract: Atrial natriuretic peptide (ANP) and two complementary peptides named brain natriuretic peptide and C-type natriuretic peptide are involved in diuresis, natriuresis, hypotension and vasorelaxation. Their actions are mediated by highly selective and specific ANP receptors. Three subtypes have been characterized and cloned: ANP receptor A, -B and -C. In the present study, the mRNA for each subtype was detected by ultrastructural in situ hybridization on ultrathin sections of Lowicryl-embedded tissue and frozen t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…2C ). In addition, several other constituents of the Neprin/Neph1 interactome were identified as specific partners of Podocin including tyrosine kinase Mer (MERTK), the single-span membrane proteins MAGI2, PTPRO, and ANPRA 43 , as well as the transporter CTL2 (Fig. 1D , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…2C ). In addition, several other constituents of the Neprin/Neph1 interactome were identified as specific partners of Podocin including tyrosine kinase Mer (MERTK), the single-span membrane proteins MAGI2, PTPRO, and ANPRA 43 , as well as the transporter CTL2 (Fig. 1D , Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the mammalian kidney, intense glomerular NPR-A cRNA hybridization was observed around the visceral surface of Bowman's capsule surrounding glomerular capillaries in epithelial and (or) mesangial cells (Wilcox et al 1991). Renal expression of NPR-A has also been documented in cells of the proximal and distal tubules (Grandclément and Morel 1998) as well as the inner medullary collecting duct cells (Yamamoto et al 1994). Collectively, the natriuretic, diuretic, and renal hemodynamic effects of BNP and other natriuretic peptides are mediated by NPR-A signaling pathways that induce increased glomerular filtration rate, as well as by the inhibition of sodium and water reabsorption at the level of the collecting duct (Kishimoto et al 1996;Shi et al 2003;McGrath et al 2005).…”
Section: B-type Natriuretic Peptide Receptor and Signalingmentioning
confidence: 99%
“…Wilcox et al found that NPR-A mRNA in kidney of rhesus was mainly expressed in glomerulus with in situ hybridization (Wilcox et al, 1991). Grandclement et al found that NPR-A mRNA and NPR-C mRNA were expressed in different sites of renal tissue, but in different degrees, with NPR-A mRNA having the richest expression in glomerulus, proximal tubule and distal tubule and NPR-C mRNA the least expression in glomerulus (Grandclement and Morel, 1998). Itoh et al with PCR technique found that the NPR-A mRNA and NPR-C mRNA were expressed in glomerulus, but their expression level were different.…”
mentioning
confidence: 99%